1992
DOI: 10.1152/ajpcell.1992.262.2.c517
|View full text |Cite
|
Sign up to set email alerts
|

Role of facilitated diffusion of calcium by calbindin in intestinal calcium absorption

Abstract: Computer simulations of transcellular Ca2+ transport in enterocytes were carried out using the simulation program SPICE. The program incorporated a negative-feedback entry of Ca2+ at the brush-border membrane that was characterized by an inhibitor constant of 0.5 microM cytosolic Ca2+ concentration ([Ca2+]). The basolateral Ca(2+)-ATPase was simulated by a four-step mechanism that resulted in Michaelis-Menten kinetics with a Michaelis constant of 0.24 microM [Ca2+]. The cytosolic diffusion of Ca2+ was simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(76 citation statements)
references
References 22 publications
3
73
0
Order By: Relevance
“…[Ca2+]j could serve as this signal, analogous to its role in th e regulation of solute transport in various epithelia [18,19]. For instance, in intestine and MDCK-F cells, [Ca2+]j has been implicated in the regulation of Ca2+ entry [2,20]. In the present study, reduction of th e basolateral efflux capacity evoked by reversal of the operation of the Na+/Ca2+ exchanger was paralleled by a m arked increase in [Ca2+].. At first sight, this observation is in agreem ent w ith the idea th at an overall increase in [Ca2'^ is responsible for the inhibition of the apical Ca2+ influx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[Ca2+]j could serve as this signal, analogous to its role in th e regulation of solute transport in various epithelia [18,19]. For instance, in intestine and MDCK-F cells, [Ca2+]j has been implicated in the regulation of Ca2+ entry [2,20]. In the present study, reduction of th e basolateral efflux capacity evoked by reversal of the operation of the Na+/Ca2+ exchanger was paralleled by a m arked increase in [Ca2+].. At first sight, this observation is in agreem ent w ith the idea th at an overall increase in [Ca2'^ is responsible for the inhibition of the apical Ca2+ influx.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the local nature of these events is, therefore, of importance and is now becoming feasible through the use of high spatial resolution confocal laser scanning microscopy [19]. Thirdly, cytosolic calbindin-D2gk levels could also control the rate of transcellular Ca2+ transport [2], In a previous study, we have implicated calbindin-D28k in the long-term control of Ca2+ reabsorption by l, 25[OH]2D3 [23], It is conceivable th at the level of calbindin-D28k determines the maximal achievable rate of transcellular Ca2+ transport, but it is rather unlikely that in short-term regulation, as investigated in th e present study, calbindinDjak represents the rate-limiting step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA level is increased as early as 3 h after the application of a dosage of 1,25-(OH) 2 D3 and the increase persists for more than 24 h. In Madin ± Darbey bovine kidney cells, it was demonstrated that calbindin-D28k mRNA was induced by 1,25-(OH) 2 D3 (10 77 M) and significantly higher levels of calbindin-D28k were observed at 8 and 24 h after induction (Gagnon et al, 1994). It is thought that calbindin-D28k present at a higher concentration in induced cells, acts as a cytosolic Ca 2+ buffer and presumably facilitates the net diffusional flux of Ca 2+ through the cytosol from the luminal to the apical side of the intestine (Feher et al, 1992). CR, the protein most closely related to calbindin-D28k (60% identity on the amino acid level) is normally not expressed in the intestine.…”
Section: Introductionmentioning
confidence: 98%
“…The active, transcellular pathway is downregulated by a diet replete in calcium (37). Luminal calcium enters the enterocyte at the microvillus border of the apical membrane via facilitated translocation through an epithelial calcium channel, either CaT1 (38) or ECaC (39); diffusion of calcium through the cell is facilitated by binding to calbindin D 9k (40), and extrusion of calcium through the basolateral membrane against an electrochemical gradient is achieved by plasma membrane Ca 2ϩ -ATPase (PMCA) (41,42).…”
mentioning
confidence: 99%